Effects of Customer Loyalty on the Profitability and the Brand Equity of the Companies in the Ports and Sez Sector - Dani, Saumil (2011)
Since the time when businesses started flourishing in the past, there has been a constant focus on maintaining healthy relationships with the customers. Customer loyalty has been a privileged concept which many companies have tried to follow and hence began the escalating strategies and tactics that companies followed to generate an increasing number of loyal customers. Since then, there have been many studies which have been conducted by experts and academicians on the topic. However, they have all been limited to the general consumer to consumer firms and there has been limited information that one manages to find about the Ports and SEZ sector. This study, hence, delves into the impact that customer loyalty has on Ports and SEZ firms, with special emphasis on the profitability and brand equity of these firms. Our literature review suggested that, in general, there are mixed feelings about the impact of customer loyalty. Many experts believe that customer loyalty can definitely have an impact on the profitability of a firm. However, some others warn about the excess expenditure that people might incur to achieve customer loyalty. Hence, one has to carefully evaluate the benefits that a loyal customer is reaping to a firm and compare it with the costs that the firm has to incur to retain this loyalty of the customer. However, the literature review did not provide information about how the therefore, break new grounds in this segment of customer loyalty evaluation for Ports and SEZ sector. The reverse, though, was available in the literature. There was information about how the brand equity of a company could help its efforts towards getting more customers and increasing customer loyalty, in general.